2021
DOI: 10.3390/cancers13215574
|View full text |Cite
|
Sign up to set email alerts
|

Type I Interferon Promotes Antitumor T Cell Response in CRPC by Regulating MDSC

Abstract: Background: Metastatic castration-resistant prostate cancer (CRPC) is the leading cause of death among prostate cancer patients. Here, our aim was to ascertain the immune regulatory mechanisms involved in CRPC development and identify potential immunotherapies against CRPC. Methods: A CRPC model was established using Myc-CaP cells in immune-competent FVB mice following castration. The immune cell profile of the tumor microenvironment (TME) was analyzed during CRPC development. Different immunotherapies were sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 61 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…ns = non-significant; ***P < 0.0001; *P < 0.01. tumor responses to DNMT inhibitor were less potent in inducing chemokine expression and did not promote MDSC recruitment. The latter is supported by findings demonstrating that IFN generally represses recruitment of MDSCs to the TME [15,51]. Together, these findings suggest that the tumor response to DNMT inhibitors may be determined by the relative involvement of IFN and IL-1 signaling and the recruitment of MDSCs to the TME.…”
Section: Discussionmentioning
confidence: 60%
“…ns = non-significant; ***P < 0.0001; *P < 0.01. tumor responses to DNMT inhibitor were less potent in inducing chemokine expression and did not promote MDSC recruitment. The latter is supported by findings demonstrating that IFN generally represses recruitment of MDSCs to the TME [15,51]. Together, these findings suggest that the tumor response to DNMT inhibitors may be determined by the relative involvement of IFN and IL-1 signaling and the recruitment of MDSCs to the TME.…”
Section: Discussionmentioning
confidence: 60%
“…IL-1β and IL-8 are involved in the recruitment of MDSC in patients with RCC [25,26]. It has been reported that MCP-1 induces MDSC accumulation [27], whereas INF-α2 suppresses MDSC accumulation [28]. Plasma levels of INF-γ and IL-10 are found to be correlated to immune-related adverse events after ICI therapy [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…While the androgen receptor still plays a crucial role in the development of castration resistance, changes in immune cells were also observed to have a distinctive action during transmission of PC disease to mCRPC 33 . It’s well known that PC and especially the late stage of the disease, CRPC, have a very complex immunosuppressive tumor microenvironment 34 .…”
Section: Discussionmentioning
confidence: 99%